Antimicrobial resistance of Shigella isolates causing traveler's diarrhea. - Vila, J (1994)
Shigella isolates were identified as a cause of traveler's diarrhea in 67 (10%) of 675 patients and were tested for resistance to seven antimicrobial agents in a comparative study with those causing nontraveler's diarrhea in Spain. Ampicillin and chloramphenicol resistance was more frequent in Shigella flexneri (60 and 46%, respectively) than in Shigella sonnei (32 and 18%, respectively) and in travel-related isolates (P < 0.05 and 0.04, respectively). Of S. sonnei isolates from patients with traveler's diarrhea, 73 and 54% showed tetracycline and trimethoprim-sulfamethoxazole resistance, respectively, compared with only 8% of isolates from patients without a history of travel to developing countries (P < 0.007 and P < 0.0002). Low-level resistance to cephalosporins was found, whereas quinolone-resistant strains were not detected among travel-related Shigella isolates. Thus, quinolones may be an effective alternative therapy for travel-related shigellosis.